FEED CONSUMPTION AND PREFERENCES OF MALE ANOAS (Bubalus spp.) AT THE ANOA BREEDING CENTER IN MANADO - Silvia Liku Ta’bi Bua’; Sonny A.E Moningkey; Meity R. Imbar; Merci R. Waani (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2026)
This study aims to measure the consumption level and analyze the feed preferences of male anoa (Bubalus spp.) kept at the Anoa Breeding Center Manado. The study was conducted for 15 days using two adult male anoa aged 7 and 11 years as research objects. The type of feed provided consisted of green fodder in the form of Pennisetum purpureum and Paspalum dilatatum and additional feed in the form of bananas, sweet potatoes, carrots and long beans with a cafeteria feeding system. Consumption data was obtained from the difference between the feed provided and the remaining feed each day, then analyzed descriptively to determine fresh consumption, dry matter consumption and organic matter consumption, while feed preferences were analyzed using Neu's Index based on dry matter consumption. The results showed that the average fresh consumption was 8729,00 and 9962,27 g/day/head, with dry matter consumption of 1293.61 and 1549.43 g/day/head, respectively, and organic matter consumption of 1188,03 and 1402,87 g/day/head. Pennisetum purpureum was the forage with the highest consumption level, although nutritionally Paspalum dilatatum had a higher dry matter content. Neu's Index value showed that supplementary feed had the highest preference (1.00), followed by Pennisetum purpureum (0.74–0.83) and Paspalum dilatatum (0.50–0.65), which was supported by the order of consumption where male anoa first chose Pennisetum purpureum in forage and hibiscus banana in supplementary feed as the most preferred feed. The results of the study showed that the physiological needs of male anoa were met with Pennisetum purpureum being preferred over Paspalum dilatatum and bananas as the most preferred supplemental feed.